Optimiranje ravnega sončnega sprejemnika z nepremičnim zrcalom - Trung, Ha Dang (Strojniški vestnik, 2000)
A new design of solar collector has been investigated which uses a reflector of the fixed type. Both collector and mirror are of the non-tracking type, so the absorbed solar energy depends on the incident angle of the solar beam and the collector-mirror arrangement. A high water temperature and a maximum in the absorbed radiation can be reached by selecting an optimal dimension ratio for the collector and reflector. The research has shown that reasonable dimension ratio of 1.7 to 3 can result in 33% to 38% more direct radiation. A flat-thin box type collector of 3.9m2 with a mirror of the same area has been tested and some initial results look promising. This model of solar collector is simpler and more efficient in regions of moderate solar radiation and useful for the absorption-refrigeration cycle.
Keywords: sprejemniki sončni; absorpcija energije; optimiranje; preskušanje; sončne celice; sprejemnik; zrcalo